Firm Value Theory and Empirical Evidence - Saona Hoffmann, Paolo (IntechOpen, 2018)
This edited volume aims to discuss the most contemporary state of the determinants of the firm value. This book presents theoretical works as well as empirical studies that contrast the arguments offered by the leading, ground-breaking theories on the firm value. What variables determine the firm value? Are these determinants controllable or uncontrollable by the managers of the companies? Is the impact of corporate governance systems on the firm value symmetrical between different institutional contexts? Do the financial reports affect the value of the firm? What role does corporate social responsibility play as a determinant of the firm value? These and other questions are analyzed and scrutinized step by step throughout this book.